The Behaviour Of Two Beam-Column Joints With Two Reinforcement Details For Use In Housing - Solís, Andrea (2023)
In housing, concrete masonry is one of the most used construction systems in Costa Rica. Under this construction system, beams and columns of equal width (12 or 15 cm) are usually required. In these cases, constructively, bending the reinforcing steel of the beam or column is used. This type of bend used“strangles” the reinforcement right in the section of maximum moment. Thus, it is relevant to experimentally investigate the behavior of these joints that are typically observed in constructions.The behavior of joints with two different reinforcement details and with 12 cm thick elements for use in housing was analyzed. Four joints were built, two with a “bottleneck” reinforcement detail(Type A Joint) and two with a 1:6 slope detail (Type B Joint). These were failed in the LanammeUCR Structures Laboratory under the application of a pseudo dynamic cyclic load. Rotations were calculated and the hysteresis curve and elastoplastic curve were constructed for each joint. The behavior of the twotypes of joints was compared, as well as the experimental capacity results with respect to the expected theoretical capacity.The results obtained show that Type A Joints do not reach the calculated theoretical capacity and present a less ductile behavior than Type B Joints. It was concluded that it is preferable and advisable to use beam-column joints with the slope detail 1:6 as part of the earthquake-resistant system of a home.